2012
DOI: 10.1016/j.cpr.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Relations among posttraumatic stress disorder, comorbid major depression, and HPA function: A systematic review and meta-analysis

Abstract: Exposure to traumatic stress is associated with increased risk for posttraumatic stress disorder (PTSD) and alterations of hypothalamic-pituitary-adrenocortical (HPA) function. Research linking traumatic stress with HPA function in PTSD has been inconsistent, however, in part due to (a) the inclusion of trauma-exposed individuals without PTSD (TE) in control groups and (b) a failure to consider comorbid major depressive disorder (MDD) and moderating variables. This meta-analysis of 47 studies (123 effect sizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
306
5
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(331 citation statements)
references
References 147 publications
(202 reference statements)
12
306
5
8
Order By: Relevance
“…Chronic stress can lead to a breakdown of the negative feedback systems of the HPA axis, promoting reduced CRH and cortisol, which profoundly affect the long-term psychological state of affected individuals. This is endorsed by a meta-analysis showing decreased CRH and cortisol levels in individuals with psychiatric illness, including PTSD (76). Although it is clear that long-term elevations in HPA activity contribute to psychopathology, the associated increases in ANG II production and the influence of ANG II on psychiatric disorders, such as PTSD, are unknown.…”
Section: The Renin-angiotensin System: Beyond Blood Pressure Controlmentioning
confidence: 99%
“…Chronic stress can lead to a breakdown of the negative feedback systems of the HPA axis, promoting reduced CRH and cortisol, which profoundly affect the long-term psychological state of affected individuals. This is endorsed by a meta-analysis showing decreased CRH and cortisol levels in individuals with psychiatric illness, including PTSD (76). Although it is clear that long-term elevations in HPA activity contribute to psychopathology, the associated increases in ANG II production and the influence of ANG II on psychiatric disorders, such as PTSD, are unknown.…”
Section: The Renin-angiotensin System: Beyond Blood Pressure Controlmentioning
confidence: 99%
“…In contrast, there is evidence that individuals with PTSD, like those with psychosis, are characterized by a blunted CAR (Chida and Steptoe, 2009). However, decreased cortisol levels during the day have been consistently reported among PTSD patients relative to controls (Morris et al, 2012). Yet another picture emerges in panic disorder patients, who show little or no alteration in basal cortisol levels and a normal CAR, but a distinctive non-responsiveness to a psychosocial stressor (Petrowski et al, 2010).…”
Section: Specificity Of Hpa Axis Abnormalities To Psychosismentioning
confidence: 99%
“…11 Even with the limitation of current methods, it has already been shown that with growing age, as well as with depression or in PTSD, the HPA axis may be subject to a 'load factor' whereby greater HPA activity in old age is accompanied by an increase in physical capacity. [12][13][14][15] Chronic changes in endogenous glucocorticoid production are typically a result of prolonged stress exposure. Patients with depression, generalized anxiety disorders or PTSD may exhibit disrupted HPA axis activity.…”
mentioning
confidence: 99%